Positive electrode active material and method for producing the same, positive electrode plate, secondary battery, battery module, battery pack, and power consumption device
A composite positive electrode active material with specific doping addresses Li/Mn defects and manganese elution in secondary batteries, enhancing cycle life and safety through improved lithium ion transmission and structural stability.
Patent Information
- Application Number
- JP2024542171
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-07-15
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-07-15
AI Technical Summary
Conventional secondary battery positive active materials like manganese lithium phosphate suffer from Li/Mn anti-site defects, manganese elution, and low cycle life and safety issues, affecting energy density and cycle performance.
A composite positive electrode active material comprising a first compound LiNi b Co d Mn e O 2 and a second compound Li a A x Mn 1-y B y P 1-z C z O 4-n D n, with specific elemental doping at Li, Mn, P, and O sites, is used to enhance lithium ion transmission, reduce elution, and improve structural stability.
The composite material significantly improves cycle performance, safety, and energy density by reducing lattice change rates, suppressing side reactions, and enhancing electronic conductivity and compaction density.
Smart Images

Figure 2025502322000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to the technical field of secondary batteries, in particular to a positive electrode active material and a manufacturing method thereof, a positive electrode plate, a secondary battery, a battery module, a battery pack and a power consuming device. [Background technology]
[0002] In recent years, as the application scope of secondary batteries becomes wider and wider, secondary batteries are widely used in energy storage power systems such as hydroelectric, thermal, wind and solar power stations, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. As secondary batteries have made great strides in development, their energy density, cycle performance and safety performance are also required to be higher. As a conventional positive electrode active material of secondary batteries, lithium manganese phosphate is prone to Li / Mn antisite defects during charging and discharging, and manganese leaching is relatively serious, which affects the gram capacity of secondary batteries and causes the safety performance and cycle performance of secondary batteries to be poor. Summary of the Invention [Problem to be solved by the invention]
[0003] The present application has been made in view of the above-mentioned problems, and aims to provide a positive electrode active material, a method for producing a positive electrode active material, a positive electrode plate, a secondary battery, a battery module, a battery pack, and a power consumption device, which solve the problems of low cycle capacity retention rate, short cycle life, and low safety of secondary batteries produced using conventional positive electrode active materials. [Means for solving the problem]
[0004] In order to achieve the above object, a first aspect of the present application provides a positive electrode active material, the positive electrode active material including a first positive electrode active material and a second positive electrode active material, The first positive electrode active material is the compound LiNi b Co d Mn e M fO2, wherein b is selected from the range of 0.314 to 0.970, d is selected from the range of 0 to 0.320, and optionally from the range of 0.047 to 0.320, e is selected from the range of 0.006 to 0.390, the sum of b, d, e and f is 1 and f is greater than 0, M is one or more elements selected from Mn, Al, Mg, Ca, Na, Ti, W, Zr, Sr, Cr, Zn, Ba, B, S and Y, and optionally M is Mg and / or Al; The second positive electrode active material is the compound Li a A x Mn 1-y B y P 1-z C z O 4-n D n wherein a is selected from the range of 0.9 to 1.1, x is selected from the range of 0.001 to 0.1, y is selected from the range of 0.001 to 0.5, z is selected from the range of 0.001 to 0.1, n is selected from the range of 0.001 to 0.1, A is one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W, B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, C is one or more elements selected from B (boron), S, Si and N, and D is one or more elements selected from S, F, Cl and Br.
[0005] Thus, the present applicant has unexpectedly discovered that the second positive electrode active material can be obtained by simultaneously doping the Li site, Mn site, P site and O site of the compound LiMnPO4 with a specific element in a specific amount, and can obtain obviously improved rate performance, and can greatly reduce the dissolution of Mn and the element doped in the Mn site, and can obtain significantly improved cycle performance and / or high temperature stability, and can also improve the gram capacity and compaction density of the material, and reduce interface side reactions. However, since the second positive electrode active material only has a one-dimensional lithium ion transmission channel, while the first positive electrode active material is a layered transition metal oxide and has a two-dimensional lithium ion transmission channel, the present application uses the first positive electrode active material and the second positive electrode active material in combination to complement the advantages of the two materials, improve the cycle capacity retention rate of the secondary battery, extend the cycle life of the secondary battery, and improve the safety of the secondary battery.
[0006] Unless otherwise noted, the chemical formula is Li a A x Mn 1-y B y P 1-z C z O 4-n D n In the above, when A is two or more elements, the above-mentioned limit on the numerical range of x is not only a limit on the stoichiometric number of each type of element that becomes A, but also a limit on the sum of the stoichiometric numbers of each element that becomes A. For example, when A is two or more elements A1, A2...An, each of the stoichiometric numbers x1, x2...xn of A1, A2...An must be within the numerical range in which x is limited by this application, and the sum of x1, x2...xn must also be within this numerical range. Similarly, when B, C and D are two or more elements, the limit on the numerical range of the stoichiometric numbers of B, C and D in this application also has the above meaning. Similarly, a compound of the chemical formula LiNi b Co d Mn e M f When M in O2 is two or more elements, the present application also includes limitations on the numerical range of the stoichiometric number of M having the above meaning.
[0007] In any embodiment, the mass of the first positive electrode active material is m1, the mass of the second positive electrode active material is m2, and the value of m1 / (m1+m2) is 2% to 55%, and optionally 3% to 50%, such that the mass percentage of the first positive electrode active material in the two positive electrode active materials is within the above range, and the stability and safety of the entire positive electrode active material can be improved.
[0008] In any of the embodiments, the value of b×m1 / (m1+m2) is 0.017 to 0.457, and optionally 0.025 to 0.415, thereby making it possible to further improve the stability and safety of the entire positive electrode active material.
[0009] In any of the embodiments, the first positive electrode active material is a single crystal or pseudo-single crystal material, and the particle size D of the first positive electrode active material is v 50 is 5.8 μm or less, optionally 2.3 to 5.8 μm, and more preferably 2.3 to 4.3 μm.
[0010] By setting the particle size of the single crystal or pseudo-single crystal first positive electrode active material within the above range, the area of the electrochemical reaction can be optimized, and the interfacial side reaction of the positive electrode during the secondary battery cycle can be further reduced and suppressed, thereby reducing the cycle decay rate of the secondary battery and extending the cycle life of the secondary battery.
[0011] In any embodiment, when the first cathode active material is a single crystal or pseudo single crystal material, d is selected from the range of 0.05 to 0.320, optionally selected from the range of 0.05 to 0.282, and / or b is greater than 0.314 and less than 0.97, and is selectively selected within the range of 0.55 to 0.869.
[0012] When the first positive electrode active material is a single crystal or pseudo-single crystal material, d and b within the above ranges are advantageous for further improving the conductivity and rate performance of the positive electrode active material, further improving the cycle capacity retention rate of the secondary battery, and further extending the cycle life of the secondary battery.
[0013] In any embodiment, when the first positive electrode active material is a polycrystalline material, the particle size D of the first positive electrode active material is v 50 is 3.5 to 13.5 μm, and / or The BET specific surface area of the first positive electrode active material is 1.32 m 2 / g or less, and selectively 0.28~1.32m 2 / g, and / or The compaction density of the first positive electrode active material at a pressure of 3 T is 2.92 g / cm 3 or more, and selectively 2.92 to 3.31 g / cm 3 It is.
[0014] By setting the particle size, specific surface area and compaction density of the polycrystalline first positive electrode active material within the above ranges, the rate performance of the positive electrode active material can be further improved, the interfacial side reaction of the positive electrode during secondary battery cycling can be further reduced and suppressed, the cycle decay rate of the secondary battery can be reduced, and the cycle life of the secondary battery can be extended.
[0015] In any embodiment, the first positive electrode active material further comprises lithium carbonate and / or lithium hydroxide; Optionally, based on the mass of the first positive electrode active material, the mass content of lithium carbonate is 1% or less and / or the mass content of lithium hydroxide is 1% or less.
[0016] Residual water molecules captured in the second positive electrode active material may react with the electrolyte to generate HF, which is likely to cause damage to the positive electrode active material itself or the SEI film on the negative electrode plate, and further affect the life of the secondary battery. The lithium carbonate and / or lithium hydroxide further contained in the first positive electrode active material of the present application can undergo a neutralization reaction with HF, reducing or suppressing the damage caused by HF to the positive electrode active material or the SEI film on the negative electrode plate, thereby further improving the cycle life of the secondary battery.
[0017] In one embodiment, in the second positive electrode active material, A is any one element selected from Zn, Al, Na, K, Mg, Nb, Mo, and W; B is at least two elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge; C is any one element selected from B (boron), S, Si, and N; D is any one element selected from S, F, Cl, and Br; Optionally, A is Mg or Nb, and / or B is at least two elements selected from Fe, Ti, V, Co and Mg, and optionally Fe and one or more elements selected from Ti, V, Co and Mg; and / or C is S, and / or D is F.
[0018] By selecting an element doped at the Li site within the above range, the lattice change rate during lithium release can be further reduced, thereby further improving the rate performance of the secondary battery. By selecting an element doped at the Mn site within the above range, the electronic conductivity can be further improved and the lattice change rate can be further reduced, thereby enhancing the rate performance and gram capacity of the secondary battery. By selecting an element doped at the P site within the above range, the rate performance of the secondary battery can be further improved. By selecting an element doped at the O site within the above range, the interface side reaction can be further reduced, thereby enhancing the high temperature performance of the secondary battery.
[0019] In any embodiment, in the second positive electrode active material, x is selected from the range of 0.001 to 0.005, and / or y is selected from the range of 0.01 to 0.5, optionally selected from the range of 0.25 to 0.5, and / or z is selected from the range of 0.001 to 0.005, and / or The value of n is selected from the range of 0.001 to 0.005.
[0020] By selecting a y value within the above range, the gram capacity and rate performance of the material can be further improved. By selecting an x value within the above range, the kinetic performance of the material can be further improved. By selecting a z value within the above range, the rate performance of the secondary battery can be further improved. By selecting an n value within the above range, the high temperature performance of the secondary battery can be further improved.
[0021] In any of the embodiments, the value of (1-y):y is selected from the range of 1 to 4, and optionally from the range of 1.5 to 3, and the value of a:x is selected from the range of 9 to 1100, and optionally from the range of 190 to 998. This can further increase the energy density and cycle performance of the positive electrode active material.
[0022] In any embodiment, the lattice change rate of the second positive electrode active material before and after the complete release of lithium is 8% or less, and optionally 4% or less. By reducing the lattice change rate, Li ions can be transmitted more easily, that is, the transition ability of Li ions in the material is stronger, which is advantageous for improving the rate performance of the secondary battery. The lattice change rate can be measured by a method known in the art, for example, X-ray diffraction spectrum (XRD).
[0023] In any embodiment, the second positive electrode active material has a Li / Mn antisite defect concentration of 2% or less, and optionally 0.5% or less. Li / Mn antisite defects are LiMnPO4 lattice defects. + and Mn 2+ The Li / Mn antisite defect concentration is the concentration of Mn in the positive electrode active material. 2+ Replaced by Li + Li + The percentage of the total amount. Antisite defects Mn 2+ Li +This is advantageous in improving the gram capacity and rate performance of the positive electrode active material by inhibiting the transfer of Li / Mn and reducing the Li / Mn antisite defect concentration. The Li / Mn antisite defect concentration can be measured by a method known in the art, for example, XRD.
[0024] In any embodiment, the surface oxygen valence of the second positive electrode active material is less than or equal to -1.82, and optionally between -1.89 and -1.98. Reducing the surface oxygen valence can reduce the interfacial side reaction between the positive electrode active material and the electrolyte, thereby improving the cycle performance and high temperature stability of the secondary battery. The surface oxygen valence can be measured by methods known in the art, for example, by electron energy loss spectroscopy (EELS).
[0025] In any embodiment, the second positive electrode active material has a packed density at 3 T of 2.0 g / cm 3 or more, and optionally 2.2 g / cm 3 That's it. The higher the packed density, the greater the weight of active material per unit volume, so improving the packed density is advantageous for improving the volumetric energy density of the cell. The packed density can be measured according to GB / T 24533-2009.
[0026] In any of the embodiments, the second active cathode material further comprises carbon, the carbon being represented by the compound Li. a A x Mn 1-y B y P 1-z C z O 4-n D n This can improve the electrical conductivity of the positive electrode active material.
[0027] A second aspect of the present application further provides a method for producing a cathode active material, the method comprising: providing a first active cathode material and a second active cathode material; mixing the first positive electrode active material with the second positive electrode active material; The first positive electrode active material is the compound LiNi b Co d Mn e M f O2, and the second positive electrode active material is the compound Li a A x Mn 1-y B y P 1-z C z O 4-n D n wherein the definitions of a, b, d, e, f, x, y, z, n, M, A, B, C and D are as described in the first aspect of the present application; Optionally, the first positive electrode active material further comprises lithium carbonate and / or lithium hydroxide; Optionally, the second positive electrode active material is a compound Li a A x Mn 1-y B y P 1-z C z O 4-n D n It further comprises carbon coated on the surface.
[0028] As a result, the present application uses a mixture of a first positive electrode active material and a second positive electrode active material to complement the advantages of the two materials, improve the cycle capacity retention rate of the secondary battery, extend the cycle life of the secondary battery, and improve the safety of the secondary battery.
[0029] A third aspect of the present application provides a positive electrode plate, the positive electrode plate including a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer including the positive electrode active material of the first aspect of the present application or the positive electrode active material produced by the method of the second aspect of the present application, and optionally, the content of the positive electrode active material in the positive electrode film layer is 10 wt % or more, and further optionally, 95 to 99.5 wt %, based on the total weight of the positive electrode film layer.
[0030] A fourth aspect of the present application provides a secondary battery, the secondary battery comprising the positive electrode active material of the first aspect of the present application or the positive electrode active material produced by the method of the second aspect of the present application or the positive electrode plate of the third aspect of the present application.
[0031] A fifth aspect of the present application provides a battery module, the battery module including the secondary battery of the fourth aspect of the present application.
[0032] A sixth aspect of the present application provides a battery pack, the battery pack including the battery module of the fifth aspect of the present application.
[0033] A seventh aspect of the present application provides a power consumption device, the power consumption device including at least one selected from a secondary battery of the fourth aspect of the present application, a battery module of the fifth aspect of the present application, and a battery pack of the sixth aspect of the present application. [Brief description of the drawings]
[0034] [Figure 1] 1 is a schematic diagram of a secondary battery according to an embodiment of the present application; [Diagram 2] FIG. 2 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. [Diagram 3] 1 is a schematic diagram of a battery module according to an embodiment of the present application; [Figure 4] 1 is a schematic diagram of a battery pack according to an embodiment of the present application; [Diagram 5] FIG. 5 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 4. [Figure 6] 1 is a schematic diagram of a power consumption device that uses a secondary battery as a power source according to an embodiment of the present application. [Figure 7] 1 is a SEM photograph of a first positive electrode active material produced in Production Example A10 of the present application. [Figure 8] 1 is a SEM photograph of a first positive electrode active material produced in Production Example A15 of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] Hereinafter, with reference to the drawings, embodiments specifically disclosing the positive electrode active material and its manufacturing method, the positive electrode plate, the secondary battery, the battery module, the battery pack, and the power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of the same structure may be omitted. This is to avoid the following description from becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.
[0036] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the end values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. It is noted that if 1 and 2 are listed as the minimum range values, and 3, 4, and 5 are listed as the maximum range values, then the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all envisaged. In this application, unless otherwise specified, a numerical range "a-b" represents a shorthand representation of any combination of real numbers a-b, where a and b are both real numbers. For example, the numerical range "0-5" represents a list of all real numbers between "0-5" already listed in this specification, and "0-5" is only a shorthand representation of combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that this parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0037] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0038] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0039] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, preferably in sequence. For example, a method including steps (a) and (b) means that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, a method described may further include step (c) means that step (c) may be added to the method in any order, e.g., the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.
[0040] Unless otherwise stated, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the listed ingredients.
[0041] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, "A or B" is satisfied if A is true (or exists) and B is false (or does not exist), if A is false (or does not exist) but B is true (or exists), or if both A and B are true (or exist).
[0042] [Secondary battery] A secondary battery is also called a rechargeable battery or storage battery, and is a battery that can be continuously used by activating the active material through charging after the battery is discharged.
[0043] In general, a secondary battery includes a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. During charging and discharging of the battery, active ions (e.g., lithium ions) are absorbed and released by shuttle between the positive electrode plate and the negative electrode plate. The separator is disposed between the positive electrode plate and the negative electrode plate, and mainly serves to prevent short circuit between the positive and negative electrodes, while allowing the active ions to pass through. The electrolyte mainly serves to conduct the active ions between the positive electrode plate and the negative electrode plate.
[0044] [Cathode active material] One embodiment of the present application provides a cathode active material, the cathode active material comprising a first cathode active material and a second cathode active material, wherein: The first positive electrode active material is the compound LiNi b Co d Mn e M f O2, wherein b is selected from the range of 0.314 to 0.970, and optionally selected from the range of 0.65 to 0.97; d is selected from the range of 0 to 0.320, and optionally selected from the range of 0.047 to 0.320 or 0.005 to 0.188; e is selected from the range of 0.006 to 0.390, and optionally selected from the range of 0.006 to 0.102; the sum of b, d, e and f is 1 and f is greater than 0; and M is one or more elements selected from Mn, Al, Mg, Ca, Na, Ti, W, Zr, Sr, Cr, Zn, Ba, B, S and Y; The second positive electrode active material is the compound Li a A x Mn 1-y B y P 1-z C z O 4-n D na is selected from the range of 0.9 to 1.1, x is selected from the range of 0.001 to 0.1, y is selected from the range of 0.001 to 0.5, z is selected from the range of 0.001 to 0.1, n is selected from the range of 0.001 to 0.1, A is one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W, and optionally Mg and / or Mo, B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and optionally one or more elements selected from V, Fe and Co, C is one or more elements selected from B (boron), S, Si and N, and optionally one or more elements selected from S, Si and N, and D is one or more elements selected from S, F, Cl and Br, and optionally F.
[0045] The first positive electrode active material is a layered transition metal oxide, which has a two-dimensional lithium ion transmission channel, and the second positive electrode active material only has a one-dimensional lithium ion transmission channel. The two are mixed and used to complement each other's advantages, thereby improving the overall electrochemical performance. The initial clone efficiency of the first positive electrode active material is generally lower than that of the second positive electrode active material. When the two are mixed and used, the secondary battery contains a large amount of reversible lithium ions even after the chemical negative electrode film is formed and consumed, improving the cycle capacity retention rate of the secondary battery, extending the cycle life of the secondary battery, and improving the safety of the secondary battery.
[0046] In addition, although the mechanism is not yet clear, the applicant unexpectedly discovered that the second positive electrode active material of the present application is obtained by element doping the compound LiMnPO4, where A, B, C and D are elements doped at the Li site, Mn site, P site and O site of the compound LiMnPO4, respectively. Without being bound by theory, the inventors of the present application discovered that the performance improvement of lithium manganese phosphate is related to the reduction of the lattice change rate and the reduction of the surface activity of lithium manganese phosphate during lithium release. The reduction of the lattice change rate reduces the lattice constant difference between the grain boundaries between the two phases, reduces the interfacial stress, and the Li +The interface transmission ability of the positive electrode active material can be reinforced, thereby improving the rate performance of the positive electrode active material. On the other hand, high surface activity is likely to cause serious interfacial side reactions, which intensify gas generation, electrolyte consumption and interface destruction, thereby affecting the performance of secondary battery cycle and other aspects. In this application, the lattice change rate is reduced by doping the Li and Mn sites. Doping the Mn site can further effectively reduce the surface activity, thereby suppressing Mn dissolution and the interface side reaction between the positive electrode active material and the electrolyte. Doping the P site can speed up the change rate of the Mn-O bond length and reduce the small polariton transition barrier of the material, thereby favoring the electronic conductivity. Doping the O site has a good effect on reducing the interface side reaction. Doping the P site and O site further affects the Mn dissolution and kinetic performance of the antisite defects. Therefore, doping can reduce the antisite defect concentration in the material, improve the kinetic performance and gram capacity of the material, and also change the topography of the particles, thereby increasing the compaction density. The applicant has unexpectedly discovered that by simultaneously doping the Li, Mn, P and O sites of the compound LiMnPO4 with specific elements in specific amounts, it is possible to obtain obviously improved rate performance, and also to significantly reduce the dissolution of Mn and the elements doped into the Mn site, thereby obtaining significantly improved cycle performance and / or high temperature stability, as well as to improve the gram capacity and compacted density of the material.
[0047] In some embodiments, M is Mg and / or Al. Doping the first positive electrode active material with Al element can increase the structural stability and thermal stability of the material and improve the cycling performance. Doping the first positive electrode active material with Mg element increases or decreases the transition metal ion valence, thereby generating holes or electrons, changing the band structure of the material, improving the intrinsic electronic conductivity of the material, and improving the cycling performance of the secondary battery. Co-doping Mg and Al into the lattice of the main body material can synergistically stabilize the material structure, improve the miscibility of the material cations, inhibit oxygen precipitation, and further improve the cycling performance and thermal stability of the secondary battery.
[0048] Unless otherwise noted, the chemical formula is Li a A x Mn 1-y B y P 1-z C z O 4-n D n In the above, when A is two or more elements, the above-mentioned limit on the numerical range of x is not only a limit on the stoichiometric number of each type of element that becomes A, but also a limit on the sum of the stoichiometric numbers of each element that becomes A. For example, when A is two or more elements A1, A2...An, each of the stoichiometric numbers x1, x2...xn of A1, A2...An must be within the numerical range in which x is limited by this application, and the sum of x1, x2...xn must also be within this numerical range. Similarly, when B, C and D are two or more elements, the limit on the numerical range of the stoichiometric numbers of B, C and D in this application also has the above meaning. Similarly, a compound of the chemical formula LiNi b Co d Mn e M f When M in O2 is two or more elements, the numerical range limitations of the stoichiometric number of M in this application also have the above meanings.
[0049] In some embodiments, the compound LiNi b Co d Mn e M f O2 and Li a A x Mn 1-y B y P 1-z C z O 4-n D n Both maintain electrical neutrality.
[0050] In some embodiments, the mass of the first positive electrode active material is m1, the mass of the second positive electrode active material is m2, and the value of m1 / (m1+m2) is 2%-55%, optionally 3%-50%, such that the mass percentage of the first positive electrode active material in the two positive electrode active materials is within the above range, and the stability and safety of the entire positive electrode active material can be improved.
[0051] In some embodiments, the value of b×m1 / (m1+m2) is 0.017 to 0.457, and optionally 0.025 to 0.415, thereby further improving the stability and safety of the entire positive electrode active material.
[0052] In some embodiments, the first active cathode material is a single crystal or pseudo-single crystal material, and the particle size D of the first active cathode material is v 50 is 5.8 μm or less, optionally 2.3 to 5.8 μm, and more preferably 2.3 to 4.3 μm.
[0053] By setting the particle size of the single crystal or pseudo-single crystal first positive electrode active material within the above range, the area of the electrochemical reaction can be optimized, and the interfacial side reaction of the positive electrode during the secondary battery cycle can be further reduced and suppressed, thereby reducing the cycle decay rate of the secondary battery and extending the cycle life of the secondary battery.
[0054] In some embodiments, the first active cathode material is a single crystal or pseudo-single crystal material, and the first active cathode material has a BET specific surface area of 1.15 m 2 / g or less, and selectively 0.45 to 1.15 m 2 / g, and / or The compaction density of the first positive electrode active material at a pressure of 3 T is 3.11 g / cm 3 or more, and selectively 3.11 to 3.4 g / cm 3 It is.
[0055] In some embodiments, when the first active cathode material is a single crystal or pseudo single crystal material, d is selected from the range of 0.05 to 0.320, optionally selected from the range of 0.05 to 0.282, and / or b is greater than 0.314 and less than 0.97, and is selectively selected within the range of 0.55 to 0.869.
[0056] When the first positive electrode active material is a single crystal or pseudo-single crystal material, d and b within the above ranges are advantageous for further improving the conductivity and rate performance of the positive electrode active material, further improving the cycle capacity retention rate of the secondary battery, and further extending the cycle life of the secondary battery.
[0057] In some embodiments, when the first active cathode material is a polycrystalline material, the particle size D of the first active cathode material is v 50 is 3.5 to 13.5 μm, and / or The BET specific surface area of the first positive electrode active material is 1.32 m 2 / g or less, and selectively 0.28~1.32m 2 / g, and / or The compaction density of the first positive electrode active material at a pressure of 3 T is 2.92 g / cm 3 or more, and selectively 2.92 to 3.31 g / cm 3 It is.
[0058] By setting the particle size, specific surface area and compaction density of the polycrystalline first positive electrode active material within the above ranges, the rate performance of the positive electrode active material can be further improved, the interfacial side reaction of the positive electrode during secondary battery cycling can be further reduced and suppressed, the cycle decay rate of the secondary battery can be reduced, and the cycle life of the secondary battery can be extended.
[0059] In some embodiments, the first active cathode material further comprises lithium carbonate and / or lithium hydroxide; Optionally, based on the mass of the first positive electrode active material, the mass content of lithium carbonate is 1% or less and / or the mass content of lithium hydroxide is 1% or less.
[0060] Residual water molecules captured in the second positive electrode active material may react with the electrolyte to generate HF, which is likely to cause damage to the positive electrode active material itself or the SEI film on the negative electrode plate, and further affect the life of the secondary battery. The lithium carbonate and / or lithium hydroxide further contained in the first positive electrode active material of the present application can undergo a neutralization reaction with HF, reducing or suppressing the damage caused by HF to the positive electrode active material or the SEI film on the negative electrode plate, thereby further improving the cycle life of the secondary battery.
[0061] In some embodiments, in the second cathode active material, A is any one element selected from Zn, Al, Na, K, Mg, Nb, Mo, and W; B is at least two elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge; C is any one element selected from B (boron), S, Si, and N; D is any one element selected from S, F, Cl, and Br; Optionally, A is Mg or Nb, and / or B is at least two elements selected from Fe, Ti, V, Co and Mg, and optionally Fe and one or more elements selected from Ti, V, Co and Mg; and / or C is S, and / or D is F.
[0062] By selecting an element doped at the Li site within the above range, the lattice change rate during lithium release can be further reduced, thereby further improving the rate performance of the secondary battery. By selecting an element doped at the Mn site within the above range, the electronic conductivity can be further improved and the lattice change rate can be further reduced, thereby enhancing the rate performance and gram capacity of the secondary battery. By selecting an element doped at the P site within the above range, the rate performance of the secondary battery can be further improved. By selecting an element doped at the O site within the above range, the interface side reaction can be further reduced, thereby enhancing the high temperature performance of the secondary battery.
[0063] In some embodiments, in the second positive electrode active material, x is selected from the range of 0.001 to 0.005; and / or y is selected from the range of 0.01 to 0.5, optionally selected from the range of 0.25 to 0.5, and / or z is selected from the range of 0.001 to 0.005, and / or The value of n is selected from the range of 0.001 to 0.005.
[0064] By selecting a y value within the above range, the gram capacity and rate performance of the material can be further improved. By selecting an x value within the above range, the kinetic performance of the material can be further improved. By selecting a z value within the above range, the rate performance of the secondary battery can be further improved. By selecting an n value within the above range, the high temperature performance of the secondary battery can be further improved.
[0065] In some embodiments, (1-y): the value of y is selected from the range of 1 to 4, and optionally from the range of 1.5 to 3, and the value of a:x is selected from the range of 9 to 1100, and optionally from the range of 190 to 998. This can further increase the energy density and cycle performance of the positive electrode active material.
[0066] In some embodiments, the lattice change rate of the second positive electrode active material before and after the complete release of lithium is 8% or less, and optionally 4% or less. By reducing the lattice change rate, Li ions can be more easily transported, i.e., the transition ability of Li ions in the material is stronger, which is advantageous for improving the rate performance of the secondary battery. The lattice change rate can be measured by a method known in the art, for example, X-ray diffraction spectrum (XRD).
[0067] In some embodiments, the second positive electrode active material has a Li / Mn antisite defect concentration of 2% or less, and optionally 0.5% or less. Li / Mn antisite defects are LiMnPO4 lattice defects. + and Mn 2+ The Li / Mn antisite defect concentration is the concentration of Mn in the positive electrode active material. 2+ Replaced by Li + Li + The percentage of the total amount. Antisite defects Mn 2+ Li + This is advantageous in improving the gram capacity and rate performance of the positive electrode active material by inhibiting the transfer of Li / Mn and reducing the Li / Mn antisite defect concentration. The Li / Mn antisite defect concentration can be measured by a method known in the art, for example, XRD.
[0068] In some embodiments, the surface oxygen valence of the second positive electrode active material is less than or equal to -1.82, and optionally between -1.89 and -1.98. Reducing the surface oxygen valence can reduce the interfacial side reaction between the positive electrode active material and the electrolyte, thereby improving the cycle performance and high temperature stability of the secondary battery. The surface oxygen valence can be measured by methods known in the art, for example, by electron energy loss spectroscopy (EELS).
[0069] In some embodiments, the second positive electrode active material has a packed density at 3 T of 2.0 g / cm 3 or more, and optionally 2.2 g / cm 3 That's it. The higher the packed density, the greater the weight of active material per unit volume, so improving the packed density is advantageous for improving the volumetric energy density of the cell. The packed density can be measured according to GB / T 24533-2009.
[0070] In some embodiments, the second active cathode material further comprises carbon, the carbon being represented by the compound Li a A x Mn 1-y B y P1-z C z O 4-n D n This can improve the electrical conductivity of the positive electrode active material.
[0071] In some embodiments, b may be, for example, 0.4, 0.5, 0.6, 0.7, 0.8, or 0.9.
[0072] In some embodiments, d may be, for example, 0.05, 0.1, 0.15, 0.2, 0.25, or 0.3.
[0073] In some embodiments, e may be, for example, 0.01, 0.02, 0.05, 0.1, 0.15, 0.2, 0.26, 0.3, or 0.35.
[0074] [Method for producing positive electrode active material] One embodiment of the present application provides a method for producing a cathode active material, the method comprising: providing a first active cathode material and a second active cathode material; mixing the first positive electrode active material with the second positive electrode active material; The first positive electrode active material is the compound LiNi b Co d Mn e M f O2, and the second positive electrode active material is the compound Li a A x Mn 1-y B y P 1-z C z O 4-n D n In this case, the definitions of a, b, d, e, f, x, y, z, n, M, A, B, C and D are as described in [Positive electrode active material], Optionally, the first positive electrode active material further comprises lithium carbonate and / or lithium hydroxide; Optionally, the second positive electrode active material is a compound Li a A x Mn 1-y B y P1-z C z O 4-n D n It further comprises carbon coated on the surface of the substrate.
[0075] As a result, the present application uses a mixture of a first positive electrode active material and a second positive electrode active material to complement the advantages of the two materials, improve the cycle capacity retention rate of the secondary battery, extend the cycle life of the secondary battery, and improve the safety of the secondary battery.
[0076] In some embodiments, the first active cathode material is prepared by the following steps. Step 1): A Ni salt, a Co salt, a Mn salt and an alkali are reacted in a solvent, and the solid phase is collected by solid-liquid separation. Step 2): Mixing the solid phase material, the lithium source, and the source of element M, ball milling, sintering, and cooling to obtain a first positive electrode active material. Optionally, in step 2), the first positive electrode active material after cooling is crushed and sieved, or the first positive electrode active material after cooling is crushed, resintered, crushed and sieved.
[0077] In some embodiments, in step 1), the reaction is carried out under conditions of a pH value of 9-13, and optionally under conditions of a pH value of 9-12 or 10-13.
[0078] In some embodiments, in step 1), the reaction temperature is between 40°C and 80°C, for example 50°C, 55°C, 60°C.
[0079] In some embodiments, in step 1), the reaction time is 8 to 70 hours, for example, 20 hours, 55 hours, 60 hours, 65 hours.
[0080] In some embodiments, in step 1), the reaction is carried out under conditions of a rotation speed of 150 to 1000 r / min, for example, 300 r / min or 500 r / min.
[0081] In some embodiments, in step 1), the solid-liquid separation is filtration.
[0082] In some embodiments, prior to step 2), the solid phase is washed, dried, and optionally vacuum dried at 100° C.-140° C. for 12-48 h, such as at 120° C. for 24 h.
[0083] In some embodiments, in step 2), the rotation speed of the ball mill is 200-500 r / s, for example, 300 r / s, 500 r / s.
[0084] In some embodiments, in step 2), the ball milling time is 1-5 h, for example, 2, 3, 4 h.
[0085] In some embodiments, in step 2), sintering is performed in an air atmosphere, optionally at 0.1-0.4 MPa.
[0086] In some embodiments, in step 2), the sintering procedure is to increase the temperature to 750°C-950°C and hold for 12-20 hours for pre-sintering, with a heating rate of 1°C / min, and optionally, decrease the temperature to 600°C at the same rate and hold for 8 hours for sintering, and after sintering, decrease the temperature to 300°C at a rate of 1°C / min.
[0087] In some embodiments, in step 2), the re-sintering procedure is to heat the material to 400°C at a rate of 20°C / min, hold the material at this temperature for 20 hours, and then cool the material to 300°C at a rate of 1°C / min after sintering.
[0088] In some embodiments, in step 2), the powder is pulverized using an airflow pulverizer, and optionally the rotation speed of the airflow pulverizer is 2500-3500 r / min, for example 3000 r / min, and optionally the air volume of the airflow pulverizer is 400-600 m 3 / h, e.g. 500m 3 / h.
[0089] In some embodiments, step 2) involves sieving through a 450-550 mesh (eg, 500 mesh) screen.
[0090] In some embodiments, the second active cathode material is prepared by the following steps. Step (1): A manganese source, a source of element B, an acid, and a selective solvent are mixed to obtain a mixture. Step (2): Mix the mixture with a lithium source, a phosphorus source, a source of element A, a source of element C, a source of element D, an optional carbon source, and an optional solvent, dry, sinter, and produce Li m A x Mn 1-y B y P 1-z C z O 4-n D n A core material containing the above is obtained. The definitions of A to D are as described above.
[0091] In some embodiments, step (1) is carried out at 60°C to 120°C, optionally 70°C to 120°C (e.g., about 60°C, about 70°C, about 80°C, about 90°C, about 100°C, about 110°C or about 120°C), and / or in step (1), the mixture is mixed by stirring at a rotation speed of 200 to 800 rpm (e.g., 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm), optionally for 1 to 9 h (further optionally for 3 to 7 h, e.g., about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours or about 9 hours).
[0092] In some embodiments, in step (2), the mixing is performed for 8 to 15 hours (e.g., about 8 hours, about 9 hours, about 10 hours, about 11 hours, about 12 hours, about 13 hours, about 14 hours, or about 15 hours), optionally at a temperature of 20 to 120°C, optionally at a temperature of 40 to 120°C (e.g., about 30°C, about 50°C, about 60°C, about 70°C, about 80°C, about 90°C, about 100°C, about 110°C, or about 120°C).
[0093] When the temperature and time in the preparation process are within the above ranges, the second positive electrode active material obtained by the preparation has relatively few lattice defects, which is advantageous in inhibiting the elution of manganese and reducing the interfacial side reaction between the positive electrode active material and the electrolyte, thereby improving the cycle performance and safety performance of the secondary battery.
[0094] In some embodiments, in step (2), the mixing is performed under a condition of pH 3.5 to 6, optionally pH 4 to 6, and further optionally pH 4 to 5. It should be noted that in the present application, the pH may be adjusted by a method commonly used in the art, for example, by adding an acid or alkali.
[0095] In some embodiments, optionally in step (2), the molar ratio of the mixture or manganese salt particles doped with element B, the lithium source, and the phosphorus source is 1:0.4-2.1:0.1-2.1, optionally about 1:0.4-0.5:0.1-1.
[0096] In some embodiments, in step (2), sintering is performed at 600 to 900°C for 4 to 10 hours, and optionally sintering may be performed at about 650°C, about 700°C, about 750°C, about 800°C, about 850°C, or about 900°C for about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours, or about 10 hours. Optionally, sintering is performed under protection of an inert gas or a mixed atmosphere of an inert gas and hydrogen gas, and more optionally, the protective atmosphere is a mixed gas of 70 to 90 volume % nitrogen gas and 10 to 30 volume % hydrogen gas, and the sintering temperature and sintering time may be within any range of any of the above values. This can improve the crystallinity, reduce the generation of heterophase, and maintain a constant particle size, thereby improving the gram capacity and compaction density of the positive electrode active material, and improving the overall performance of the secondary battery, including the rate performance.
[0097] In some optional embodiments, the mixture obtained in step (1) is filtered, dried, and ground to form a powder doped with element B having a particle size D vManganese salt particles having a particle size of 50 to 200 nm are obtained. The manganese salt particles doped with element B are used in step (2) to mix with a lithium source, a phosphorus source, a source of element A, a source of element C, a source of element D, and a selective solvent.
[0098] In some optional embodiments, step (2) involves drying using a spray drying device.
[0099] In some optional embodiments, in step (2), grinding is performed simultaneously with mixing.
[0100] The manufacturing method of the present application is not particularly limited with respect to the origin of the material, and the origin of a certain element may include one or more of the element's simple substance, sulfate, halide, nitrate, phosphate, oxalate, carbonate, oxide, and hydroxide, provided that the origin can achieve the objective of the manufacturing method of the present application.
[0101] In some embodiments, the source of element A is one or more selected from the group consisting of an element, an oxide, a phosphate, an oxalate, a carbonate, and a sulfate of element A; and / or the source of element B is one or more selected from the group consisting of an element, an oxide, a phosphate, an oxalate, a carbonate and a sulfate of element B; and / or the source of element C is one or more selected from sulfates, borates, nitrates and silicates of element C; and / or The source of element D is one or more selected from a simple substance and an ammonium salt of element D.
[0102] In some embodiments, the source of element M is one or more selected from the group consisting of an elemental salt, a carbonate, a sulfate, a halide, a nitrate, an organic acid salt, an oxide, and a hydroxide of element M.
[0103] The amount of each of the sources of elements A, B, C, D, and M added depends on the target doping amount, and the ratio of the amount of the lithium source, manganese source, and phosphorus source used is in accordance with the stoichiometric ratio.
[0104] In the present application, the manganese source may be any manganese-containing material known in the art that can be used to prepare lithium manganese phosphate. By way of example, the manganese source may be one or more selected from elemental manganese, manganese dioxide, manganese phosphate, manganese oxalate, and manganese carbonate.
[0105] In the present application, the acid may be one or more selected from hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, organic acids such as silicic acid, metasilicic acid, and organic acids such as oxalic acid. In some embodiments, the acid is a dilute organic acid having a concentration of 60% by weight or less.
[0106] In the present application, the lithium source may be any lithium-containing material known in the art that can be used to prepare lithium manganese phosphate. By way of example, the lithium source may be one or more selected from lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate.
[0107] In the present application, the phosphorus source may be any phosphorus-containing material known in the art that can be used to prepare lithium manganese phosphate. By way of example, the phosphorus source may be one or more selected from diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, and phosphoric acid.
[0108] In the present application, by way of example, the carbon source is one or more selected from starch, sucrose, glucose, polyvinyl alcohol, polyethylene glycol, citric acid.
[0109] [Positive electrode plate] The positive electrode plate generally includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the above-mentioned positive electrode active material or the positive electrode active material produced by the above-mentioned method.
[0110] For example, a positive electrode current collector has two opposing surfaces in the thickness direction of the positive electrode current collector, and a positive electrode film layer is disposed on either one or both of the two opposing surfaces of the positive electrode current collector.
[0111] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, an aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0112] In some embodiments, the positive electrode membrane layer further optionally includes an adhesive. For example, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0113] In some embodiments, the positive electrode membrane layer further optionally includes a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, by way of example.
[0114] In some embodiments, the positive electrode plate can be manufactured in the following manner: The components for manufacturing the positive electrode plate, such as the positive electrode active material, the conductive agent, the adhesive, and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, which is then coated on a positive electrode current collector, and the positive electrode plate is obtained after processes such as drying and cold pressing.
[0115] [Negative electrode plate] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.
[0116] For example, the negative electrode current collector has two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on either one or both of the two opposing surfaces of the negative electrode current collector.
[0117] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, the metal foil sheet may be a copper foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0118] In some embodiments, the negative electrode active material may be a negative electrode active material used in batteries known in the art. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicone-based materials, tin-based materials, and lithium titanate. The silicone-based material may be selected from at least one of silicone alone, silicone oxide, silicone carbon composite, silicone nitrogen composite, and silicone alloy. The tin-based material may be selected from at least one of tin alone, tin oxide, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as battery negative electrode active materials may be used. These negative electrode active materials may be used alone or in combination of two or more.
[0119] In some embodiments, the negative electrode membrane layer further optionally includes an adhesive, which may be selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS), for example.
[0120] In some embodiments, the negative electrode film layer further optionally includes a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, by way of example.
[0121] In some embodiments, the negative electrode membrane layer optionally further comprises other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).
[0122] In some embodiments, the negative electrode plate can be manufactured in the following manner: Components for manufacturing the negative electrode plate, such as a negative electrode active material, a conductive agent, an adhesive, and any other components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, which is then coated on a negative electrode current collector, and the negative electrode plate is obtained after processes such as drying and cold pressing.
[0123] [Electrolyte] The electrolyte serves to conduct ions between the positive and negative electrodes. The present application is not specifically limited to the type of electrolyte, which can be selected according to need. For example, the electrolyte may be liquid, gel, or all solid.
[0124] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent. In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.
[0125] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.
[0126] In some embodiments, the electrolyte solution further optionally includes additives. For example, the additives may include an anode film-forming additive, a cathode film-forming additive, and may further include additives that can improve some performance of the battery, such as an additive that improves the overcharge performance of the battery, an additive that improves the high temperature or low temperature performance of the battery, etc.
[0127] [Separator] In some embodiments, the secondary battery further includes a separator. The present application is not particularly limited to the type of separator, and any known porous structure separator having good chemical stability and mechanical stability may be selected.
[0128] In some embodiments, the material of the separator may be at least one selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single layer film or a multi-layer composite film, and there is no particular limitation. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, and there is no particular limitation.
[0129] In some embodiments, the positive plates, negative plates and separators can be fabricated into an electrode assembly by a winding process or a lamination process.
[0130] In some embodiments, the secondary battery may include an exterior body, which may be used to package the electrode assembly and the electrolyte.
[0131] In some embodiments, the exterior of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a pouch, such as a bag-shaped pouch. The material of the pouch may be plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0132] The present application is not particularly limited to the shape of the secondary battery, which may be cylindrical, rectangular or any other shape. For example, FIG. 1 shows a secondary battery 5 having a rectangular structure as an example.
[0133] In some embodiments, referring to FIG. 2, the exterior body may include a case 51 and a cover plate 53. Here, the case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 can cover the opening to seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator can form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. The electrolyte is infiltrated into the electrode assembly 52. The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and those skilled in the art can select it according to the actual needs.
[0134] In some embodiments, the secondary batteries may be assembled into a battery module, and the number of secondary batteries included in the battery module may be one or more, with the specific number being selectable by one skilled in the art depending on the application and capacity of the battery module.
[0135] Fig. 3 shows an example of a battery module 4. Referring to Fig. 3, in the battery module 4, the multiple secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by fasteners.
[0136] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.
[0137] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number can be selected by one skilled in the art according to the application and capacity of the battery pack.
[0138] 4 and 5 show an example of a battery pack 1. Referring to Fig. 4 and Fig. 5, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box may include an upper housing 2 and a lower housing 3, and the upper housing 2 may cover the lower housing 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0139] The present application further provides a power consuming device, which includes at least one of the secondary battery, battery module, or battery pack according to the present application. The secondary battery, battery module, or battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0140] As the power consuming device, a secondary battery, a battery module, or a battery pack can be selected according to the usage demand.
[0141] 6 shows an example of a power consumption device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be employed to meet the demand for high power output and high energy density of the secondary battery of the power consumption device.
[0142] [Example] The following describes the examples of the present application. The examples described below are illustrative and are used only to interpret the present application, and should not be understood as limitations on the present application. If no specific techniques or conditions are specified in the examples, they are performed according to the techniques or conditions described in the literature in the field or according to the product specifications. If no manufacturer is specified, the reagents or equipment used are all ordinary products available on the market.
[0143] Preparation of the first positive electrode active material [Manufacturing example A3]:LiNi 0.55 Co 0.113 Mn 0.277 Al 0.04 Mg 0.02 O2 (single crystal-like) (1) A mixed solution was prepared by adding water to NiSO4, CoSO4 and MnSO4 in a molar ratio of 0.55:0.113:0.277. The concentration of NiSO4 in the mixed solution was 2 mol / L, and a 5 mol / L NaOH solution was prepared. (2) 50L of the mixed solution was introduced into the reaction tank, and 50L of NaOH solution and an appropriate amount of 0.5mol / L of ammonia aqueous solution were further introduced into the reaction tank. The pH value in the reaction tank was set to 9.0-12.0, the reaction temperature was set to 40℃-80℃, and the reaction was carried out under stirring conditions for 60 hours. The stirring rotation speed was set to 300-1000r / min. After completion, the precipitate was filtered and washed, and the washed precipitate was vacuum dried at 120℃ for 24 hours to obtain a precursor. (3) Li2CO3, precursor, Al2O3 and MgO were mixed. Here, the molar ratio of Li2CO3 (in terms of the molar amount of Li element), precursor (in terms of the total molar amount of the three elements Ni, Co and Mn in the mixed solution), Al2O3 (in terms of the molar amount of Al element) and MgO was 1.05:0.94:0.04:0.02. After mixing, it was placed in a ball mill tank and ball milled at a rotation speed of 300 r / s for 2 hours, and then placed in a van-type furnace and pre-sintered by heating to 950 °C in an air atmosphere of 0.2 MPa and keeping the temperature for 12 hours. The heating rate was 1 °C / min. Then, the temperature was lowered to 600 °C at a rate of 1 °C / min and kept at that temperature for 8 hours for sintering. After sintering, the temperature was lowered to 300 °C at a rate of 1 °C / min, followed by natural cooling to room temperature, and then passed through an air flow mill and sintered at a rotation speed of 3000 r / min for 500 m. 3 / h, crushed for 0.5 h, and sieved through a 500 mesh screen to obtain a first positive electrode active material.
[0144] [Manufacturing example A16]:LiNi 0.83 Co 0.114 Mn 0.006 Al 0.04 Mg 0.01 O2 (polycrystalline) (1) A mixed solution was prepared by adding water to NiSO4, CoSO4 and MnSO4 in a molar ratio of 0.83:0.114:0.006. The concentration of NiSO4 in the mixed solution was 2 mol / L, and a 6 mol / L NaOH solution was prepared. (2) 50L of the mixed solution was introduced into the reaction tank, and 50L of NaOH solution and an appropriate amount of 0.5mol / L ammonia aqueous solution were further introduced into the reaction tank. The pH value in the reaction tank was set to 10-13, the reaction temperature was set to 40℃-80℃, and the reaction was carried out under stirring conditions for 8-20 hours. The stirring rotation speed was set to 150-300r / min. After completion, the precipitate was filtered and washed, and the washed precipitate was vacuum dried at 120℃ for 24 hours to obtain a precursor. (3) LiOH, precursor, Al2O3 and MgO were mixed. Here, the molar ratio of LiOH, precursor (converted to the total molar amount of the three elements Ni, Co and Mn in the mixed solution), Al2O3 (converted to the molar amount of Al element) and MgO was 1.05:0.95:0.04:0.01. After mixing, it was placed in a ball mill tank and ball milled at a rotation speed of 500 r / s for 2 hours, and then placed in a van furnace and pre-sintered by heating to 750°C in an air atmosphere of 0.2 MPa and keeping the temperature for 20 hours. The heating rate was 20°C / min. After sintering, the temperature is lowered to 300°C at a rate of 1°C / min, then naturally cooled to room temperature, and crushed at a rotation speed of 2000r / min for 5 hours. The mixture is then heated to 400°C at a rate of 20°C / min and kept at that temperature for 20 hours before sintering. After sintering, the temperature is lowered to 300°C at a rate of 1°C / min, then naturally cooled to room temperature, and then passed through an airflow crusher at a rotation speed of 3000r / min for 500m. 3 / h, crushed for 0.5 h, and sieved through a 400 mesh screen to obtain a first positive electrode active material.
[0145] [Production Examples A1, A2, A4 to A15, A17 to A22 and Comparative Production Example A1] The first positive electrode active materials of Preparation Examples A1, A2, A4 to A11, and A22 and Comparative Preparation Example A1 were prepared in a manner similar to Preparation Example A3. The differences in the preparation are shown in Table 1, and the rest are the same as Preparation Example A3. Manufacturing Examples A12 to A15 and A17 to A21 were manufactured in a manner similar to Manufacturing Example A16. The differences in the manufacturing process are shown in Table 1, and the rest are the same as Manufacturing Example A16.
[0146] [Table 1] JPEG2025502322000003.jpg173169 JPEG2025502322000004.jpg175169 JPEG2025502322000005.jpg154169
[0147] Preparation of second positive electrode active material [Manufacturing example B1] Preparation of doped manganese oxalate: 1.3 mol MnSO4·H2O and 0.7 mol FeSO4·H2O were mixed thoroughly in a blender for 6 hours, the mixture was transferred to a reaction vessel, 10 L deionized water and 2 mol oxalic acid dihydrate were added, and the mixture was heated to 80°C. After stirring at a rotation speed of 600 rpm for 6 hours, the reaction was completed (no bubbles were generated) and a suspension of Fe-doped manganese oxalate was obtained. The suspension was filtered, and the cake was dried at 120°C and crushed to obtain a particle size of D v Fe-doped manganese oxalate particles with sizes of about 50 to 100 nm were obtained. Preparation of doped lithium manganese phosphate: 1 mol Fe-doped manganese oxalate particles, 0.497 mol lithium carbonate, 0.001 mol Mo(SO4)3, 0.999 mol phosphoric acid containing 85% phosphoric acid aqueous solution, 0.001 mol H4SiO4, 0.0005 mol NH4HF2 and 0.005 mol sucrose were added to 20 L of deionized water, the mixture was transferred to a sand mill and thoroughly ground and stirred for 10 hours to obtain a slurry. The slurry was transferred to a spray drying machine for spray drying granulation, the drying temperature was set to 250 °C, and dried for 4 hours to obtain particles. The particles were sintered at 700 °C for 10 hours in a nitrogen gas (90% v / v) + hydrogen gas (10% v / v) protective atmosphere to obtain the second positive electrode active material, carbon-coated Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 S 0.001 O 3.999 F 0.001 The element content of the positive electrode active material can be detected by inductively coupled plasma emission spectroscopy (ICP).
[0148] [Manufacturing example B2] The amount of high purity Li2CO3 was changed to 0.4885 mol, Mo(SO4)3 was replaced with an equimolar amount of MgSO4, the amount of FeSO4·H2O was changed to 0.68 mol, 0.02 mol of Ti(SO4)2 was added when preparing doped manganese oxalate, and H4SiO4 was replaced with an equimolar amount of HNO3, which was the same as Preparation Example B1.
[0149] [Manufacturing Example B3] The same as Preparation Example B1, except that the amount of high purity Li2CO3 was changed to 0.496 mol, Mo(SO4)3 was replaced with an equimolar amount of W(SO4)3, and H4SiO4 was replaced with an equimolar amount of H2SO4.
[0150] [Manufacturing example B4] The same as Preparation Example B1, except that the amount of high purity Li2CO3 was changed to 0.4985 mol, 0.001 mol of Mo(SO4)3 was replaced by 0.0005 mol of Al2(SO4)3, and NH4HF2 was replaced by an equal molar amount of NH4HCl2.
[0151] [Manufacturing example B5] The procedure was the same as Preparation Example B1, except that the amount of FeSO4·H2O was changed from 0.7 mol to 0.69 mol, 0.01 mol VCl2 was further added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.4965 mol, 0.001 mol Mo(SO4)3 was changed to 0.0005 mol Nb2(SO4)5, and H4SiO4 was changed to an equal molar amount of H2SO4.
[0152] [Manufacturing example B6] The amount of FeSO4·H2O was changed to 0.68 mol, 0.01 mol VCl2 and 0.01 mol MgSO4 were added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.4965 mol, 0.001 mol Mo(SO4)3 was replaced with 0.0005 mol Nb2(SO4)5, and H4SiO4 was replaced with an equal molar amount of H2SO4, but this was the same as Preparation B1.
[0153] [Manufacturing example B7] The procedure is the same as Preparation B6, except that MgSO4 was replaced with an equimolar amount of CoSO4.
[0154] [Manufacturing example B8] The procedure is the same as Preparation B6, except that MgSO4 was replaced with an equimolar amount of NiSO4.
[0155] [Manufacturing example B9] The amount of FeSO4·H2O was changed to 0.698 mol, 0.002 mol of Ti(SO4)2 was further added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.4955 mol, 0.001 mol of Mo(SO4)3 was replaced with 0.0005 mol of Nb2(SO4)5, H4SiO4 was replaced with an equimolar amount of H2SO4, and NH4HF2 was replaced with an equimolar amount of NH4HCl2, which was the same as Preparation Example B1.
[0156] [Manufacturing Example B10] The amount of FeSO4·H2O was changed to 0.68 mol, 0.01 mol VCl2 and 0.01 mol MgSO4 were added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.4975 mol, 0.001 mol Mo(SO4)3 was replaced with 0.0005 mol Nb2(SO4)5, and NH4HF2 was replaced with an equimolar amount of NH4HBr2, except that the amount of FeSO4·H2O was changed to 0.68 mol, 0.01 mol VCl2 and 0.01 mol MgSO4 were added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.4975 mol, 0.001 mol Mo(SO4)3 was replaced with 0.0005 mol Nb2(SO4)5, and NH4HF2 was replaced with an equimolar amount of NH4HBr2.
[0157] [Manufacturing example B11] The same as Preparation B1, except that the amount of FeSO4·H2O was changed to 0.69 mol, 0.01 mol of VCl2 was added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.499 mol, Mo(SO4)3 was replaced with an equimolar amount of MgSO4, and NH4HF2 was replaced with an equimolar amount of NH4HBr2.
[0158] [Manufacturing example B12] The same as Preparation B1, except that the amount of MnSO4·H2O was changed to 1.36 mol, the amount of FeSO4·H2O was changed to 0.6 mol, 0.04 mol of VCl2 was added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.4985 mol, Mo(SO4)3 was replaced with an equimolar amount of MgSO4, and H4SiO4 was replaced with an equimolar amount of HNO3.
[0159] [Manufacturing example B13] The procedure is the same as Example B12, except that the amount of MnSO4·H2O was changed to 1.16 mol and the amount of FeSO4·H2O was changed to 0.8 mol.
[0160] [Manufacturing example B14] This is the same as Example B12, except that the amount of MnSO4·H2O was changed to 1.3 mol and the amount of VCl2 was changed to 0.1 mol.
[0161] [Manufacturing example B15] The amount of MnSO4·H2O was changed to 1.2 mol, 0.1 mol of VCl2 was added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.494 mol, 0.001 mol of Mo(SO4)3 was replaced with 0.005 mol of MgSO4, and H4SiO4 was replaced with an equal molar amount of H2SO4, which was the same as Preparation B1.
[0162] [Manufacturing example B16] The amount of MnSO4·H2O was changed to 1.2 mol, 0.1 mol of VCl2 was added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.467 mol, 0.001 mol of Mo(SO4)3 was replaced with 0.005 mol of MgSO4, 0.001 mol of H4SiO4 was replaced with 0.005 mol of H2SO4, and 1.175 mol of 85% phosphoric acid was replaced with 1.171 mol of 85% phosphoric acid.
[0163] [Manufacturing example B17] The amount of MnSO4·H2O was changed to 1.2 mol, 0.1 mol of VCl2 was added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.492 mol, 0.001 mol of Mo(SO4)3 was replaced with 0.005 mol of MgSO4, H4SiO4 was replaced with an equal molar amount of H2SO4, and 0.0005 mol of NH4HF2 was replaced with 0.0025 mol.
[0164] [Manufacturing example B18] The amount of FeSO4·H2O was changed to 0.5 mol, 0.1 mol of VCl2 and 0.1 mol of CoSO4 were added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.492 mol, 0.001 mol of Mo(SO4)3 was replaced with 0.005 mol of MgSO4, H4SiO4 was replaced with an equal molar amount of H2SO4, and 0.0005 mol of NH4HF2 was replaced with 0.0025 mol.
[0165] [Manufacturing example B19] This is the same as Example B18, except that the amount of FeSO4·H2O was changed to 0.4 mol and 0.1 mol of CoSO4 was changed to 0.2 mol.
[0166] [Manufacturing example B20] The same as Preparation B18, except that the amount of MnSO4·H2O was changed to 1.5 mol, the amount of FeSO4·H2O was changed to 0.1 mol, and the amount of CoSO4 was changed to 0.3 mol.
[0167] [Manufacturing example B21] The same as Preparation B18, except that 0.1 mol of CoSO4 was replaced with 0.1 mol of NiSO4.
[0168] [Manufacturing example B22] The same as Preparation B18, except that the amount of MnSO4·H2O was changed to 1.5 mol, the amount of FeSO4·H2O was changed to 0.2 mol, and 0.1 mol of CoSO4 was replaced by 0.2 mol of NiSO4.
[0169] [Manufacturing example B23] The same as Preparation B18, except that the amount of MnSO4·H2O was changed to 1.4 mol, the amount of FeSO4·H2O was changed to 0.3 mol, and the amount of CoSO4 was changed to 0.2 mol.
[0170] [Production Example B24] The procedure was the same as Preparation Example B1, except that 1.3 mol of MnSO4·H2O was changed to 1.2 mol, 0.7 mol of FeSO4·H2O was changed to 0.5 mol, 0.1 mol of VCl2 and 0.2 mol of CoSO4 were added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.497 mol, 0.001 mol of Mo(SO4)3 was changed to 0.005 mol of MgSO4, H4SiO4 was changed to the same molar amount of H2SO4, and 0.0005 mol of NH4HF2 was changed to 0.0025 mol.
[0171] [Manufacturing example B25] The same as Preparation B18, except that the amount of MnSO4·H2O was changed to 1.0 mol, the amount of FeSO4·H2O was changed to 0.7 mol, and the amount of CoSO4 was changed to 0.2 mol.
[0172] [Manufacturing example B26] The amount of MnSO4·H2O was changed to 1.4 mol, the amount of FeSO4·H2O was changed to 0.3 mol, 0.1 mol of VCl2 and 0.2 mol of CoSO4 were added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.4825 mol, 0.001 mol of Mo(SO4)3 was replaced with 0.005 mol of MgSO4, the amount of H4SiO4 was changed to 0.1 mol, the amount of phosphoric acid was changed to 0.9 mol, and the amount of NH4HF2 was changed to 0.04 mol, which is the same as Preparation Example B1.
[0173] [Manufacturing example B27] The amount of MnSO4·H2O was changed to 1.4 mol, the amount of FeSO4·H2O was changed to 0.3 mol, 0.1 mol of VCl2 and 0.2 mol of CoSO4 were added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.485 mol, 0.001 mol of Mo(SO4)3 was replaced with 0.005 mol of MgSO4, the amount of H4SiO4 was changed to 0.08 mol, the amount of phosphoric acid was changed to 0.92 mol, and the amount of NH4HF2 was changed to 0.05 mol. This is the same as Preparation Example B1.
[0174] [Manufacturing example B28-B41] The positive electrode active material was produced in the same manner as in Production Example B1, but the stirring rotation speed, temperature, grinding and stirring time in a sand mill, sintering temperature and sintering time when producing doped manganese oxalate were changed, as shown in Table 2 below.
[0175] [Table 2]
[0176] [Production Examples B42-B54] The positive electrode active material was prepared in the same manner as in Preparation Example B1, but the lithium source, manganese source, phosphorus source, and the doped sources of elements A, B, C, and D were changed, as shown in Table 3 below. The composition of the positive electrode active material prepared was the same as in Preparation Example B1, that is, all Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 S 0.001 O 3.999 F 0.001 It is.
[0177] [Table 3]
[0178] [Manufacturing example B55] (1) Preparation of doped manganese oxalate 1.2 mol of MnSO4·H2O and 0.79 mol of FeSO4·H2O were mixed thoroughly in a blender for 6 hours, the mixture was transferred to a reaction vessel, 10 L of deionized water, 2 mol of oxalic acid dihydrate, and 0.01 mol of VCl2 were added, and the mixture was heated to 80°C. After stirring at a rotation speed of 600 rpm for 6 hours, the reaction was completed (no bubbles were generated) and a suspension of Fe-doped manganese oxalate was obtained. The suspension was filtered, and the cake was dried at 120°C and crushed to obtain a particle size of D v Fe-doped manganese oxalate particles with sizes of about 50 to 100 nm were obtained.
[0179] (2) Preparation of doped lithium manganese phosphate 1 mol Fe-doped manganese oxalate particles, 0.45 mol lithium carbonate, 0.05 mol MgSO4, 0.9 mol phosphoric acid containing 85% phosphoric acid aqueous solution, 0.1 mol H4SiO4, 0.05 mol NH4HF2 and 0.005 mol sucrose were added to 20 L of deionized water, the mixture was transferred to a sand mill and thoroughly ground and stirred for 10 hours to obtain a slurry. The slurry was transferred to a spray drying machine for spray drying granulation, the drying temperature was set to 250 °C, and dried for 4 hours to obtain particles. The particles were sintered at 700 °C for 10 hours in a nitrogen gas (90% v / v) + hydrogen gas (10% v / v) protective atmosphere to obtain a positive electrode active material. The element content was detected using inductively coupled plasma emission spectroscopy (ICP), and the chemical formula Li 0.9 Mg 0.05 Mn 0.6 Fe 0.395 V 0.005 P 0.9 S 0.1 O 3.9 F 0.1 obtained.
[0180] [Manufacturing example B56] In step (2), the lithium carbonate was 0.55 mol, the MgSO4 was 0.001 mol, and the NH4HF2 was 0.001 mol. Except for this, the same as in Example B55, and the positive electrode active material Li 1.1 Mg 0.001 Mn 0.6 Fe 0.395V 0.005 P 0.9 S 0.1 O 3.998 F 0.002 obtained.
[0181] [Manufacturing example B57] In step (2), the MgSO4 was 0.1 mol, the 85% phosphoric acid aqueous solution contained 0.95 mol of phosphoric acid, the H4SiO4 was 0.05 mol, and the NH4HF2 was 0.025 mol. The same as in Preparation B55, 0.9 Mg 0.1 Mn 0.6 Fe 0.395 V 0.005 P 0.95 S 0.05 O 3.95 F 0.05 obtained.
[0182] [Manufacturing example B58] The same as in Preparation B55, except that in step (1), MnSO4·H2O was 1.998 mol, FeSO4·H2O was 0.002 mol, and VCl2 was not used, and in step (2), lithium carbonate was 0.475 mol, the 85% phosphoric acid aqueous solution contained 0.96 mol of phosphoric acid, H4SiO4 was 0.04 mol, and NH4HF2 was 0.01 mol. 0.95 Mg 0.05 Mn 0.999 Fe 0.001 P 0.96 S 0.04 O 3.99 F 0.01 obtained.
[0183] [Production Example B59] The same as in Manufacturing Example B55, except that in step (1), MnSO4·H2O was 1.98 mol, FeSO4·H2O was 0.02 mol, and VCl2 was not used, and in step (2), lithium carbonate was 0.475 mol, the 85% phosphoric acid aqueous solution contained 0.96 mol of phosphoric acid, H4SiO4 was 0.04 mol, and NH4HF2 was 0.01 mol.0.95 Mg 0.05 Mn 0.99 Fe 0.01 P 0.96 S 0.04 O 3.99 F 0.01 obtained.
[0184] [Manufacturing example B60] The same as in Preparation B55, except that in step (1), MnSO4·H2O was 1.6 mol, FeSO4·H2O was 0.4 mol, and VCl2 was not used, and in step (2), lithium carbonate was 0.475 mol, the 85% phosphoric acid aqueous solution contained 0.96 mol of phosphoric acid, H4SiO4 was 0.04 mol, and NH4HF2 was 0.01 mol. 0.95 Mg 0.05 Mn 0.8 Fe 0.2 P 0.96 S 0.04 O 3.99 F 0.01 obtained.
[0185] [Comparative manufacturing example B1] Preparation of manganese oxalate: 1 mol of MnSO4·H2O was added to the reaction vessel, and 10 L of deionized water and 1 mol of oxalic acid dihydrate (in terms of oxalic acid) were added. The reaction vessel was heated to 80°C and stirred at a rotation speed of 600 rpm for 6 hours. The reaction was completed (no bubbles were generated) and a manganese oxalate suspension was obtained. The suspension was then filtered, and the cake was dried at 120°C and then crushed to obtain a median particle size D v Manganese oxalate particles with sizes ranging from 50 to 200 nm were obtained.
[0186] Preparation of lithium manganese phosphate: 1 mol of the above manganese oxalate particles, 0.5 mol of lithium carbonate, 1 mol of phosphoric acid in 85% aqueous phosphoric acid solution, and 0.005 mol of sucrose were added to 20 L of deionized water. The mixture was transferred to a sand mill and thoroughly ground and stirred for 10 hours to obtain a slurry. The slurry was transferred to a spray drying device and spray-dried and granulated, and the drying temperature was set to 250°C and dried for 4 hours to obtain particles. The above powder was sintered at 700°C for 10 hours in a protective atmosphere of nitrogen gas (90% by volume) + hydrogen gas (10% by volume) to obtain carbon-coated LiMnPO4.
[0187] [Comparative manufacturing example B2] Comparative Example 1 was the same as Comparative Example B1, except that 1 mol of MnSO4·H2O was replaced with 0.85 mol of MnSO4·H2O and 0.15 mol of FeSO4·H2O, which were added to the blender and mixed thoroughly for 6 hours, and then added back to the reactor.
[0188] [Comparative manufacturing example B3] The same as Preparation B1 except that the amount of MnSO4·H2O was changed to 1.9 mol, 0.7 mol of FeSO4·H2O was replaced with 0.1 mol of ZnSO4, the amount of Li2CO3 was changed to 0.495 mol, 0.001 mol of Mo(SO4)3 was replaced with 0.005 mol of MgSO4, the amount of phosphoric acid was changed to 1 mol, and H4SiO4 and NH4HF2 were not added.
[0189] [Comparative manufacturing example B4] The same as Preparation B1 except that the amount of MnSO4·H2O is changed to 1.2 mol, the amount of FeSO4·H2O is changed to 0.8 mol, the amount of Li2CO3 is changed to 0.45 mol, 0.001 mol of Mo(SO4)3 is changed to 0.005 mol of Nb2(SO4)5, 0.999 mol of phosphoric acid is changed to 1 mol, 0.0005 mol of NH4HF2 is changed to 0.025 mol, and no H4SiO4 is added.
[0190] [Comparative manufacturing example B5] The same as Preparation B1 except that the amount of MnSO4·H2O was changed to 1.4 mol, the amount of FeSO4·H2O was changed to 0.6 mol, the amount of Li2CO3 was changed to 0.38 mol, and 0.001 mol of Mo(SO4)3 was replaced by 0.12 mol of MgSO4.
[0191] [Comparative manufacturing example B6] The same as Preparation B1, except that the amount of MnSO4·H2O was changed to 0.8 mol, 0.7 mol of FeSO4·H2O was replaced with 1.2 mol of ZnSO4, the amount of Li2CO3 was changed to 0.499 mol, and 0.001 mol of Mo(SO4)3 was replaced with 0.001 mol of MgSO4.
[0192] [Comparative manufacturing example B7] The same as Preparation B1, except that the amount of MnSO4·H2O was changed to 1.4 mol, the amount of FeSO4·H2O was changed to 0.6 mol, the amount of Li2CO3 was changed to 0.534 mol, 0.001 mol of Mo(SO4)3 was changed to 0.001 mol of MgSO4, the amount of phosphoric acid was changed to 0.88 mol, the amount of H4SiO4 was changed to 0.12 mol, and the amount of NH4HF2 was changed to 0.025 mol.
[0193] [Comparative manufacturing example B8] The same as Preparation B1, except that the amount of MnSO4·H2O was changed to 1.2 mol, the amount of FeSO4·H2O was changed to 0.8 mol, the amount of Li2CO3 was changed to 0.474 mol, 0.001 mol of Mo(SO4)3 was changed to 0.001 mol of MgSO4, the amount of phosphoric acid was changed to 0.93 mol, the amount of H4SiO4 was changed to 0.07 mol, and the amount of NH4HF2 was changed to 0.06 mol.
[0194] Manufacturing of mixed positive electrode active material [Examples 1 to 43 and Comparative Example 1] The first positive electrode active material and the second positive electrode active material are stirred and mixed in a stirring tank. The mass of the first positive electrode active material is m1, the mass of the second positive electrode active material is m2, and the mass of the mixed positive electrode active material is m1+m2.
[0195] The parameters of each of the examples and comparative examples are shown in Table 4.
[0196] [Table 4] JPEG2025502322000009.jpg190169
[0197] Full battery production The positive electrode active material, acetylene black as a conductive agent, and polyvinylidene fluoride (PVDF) as an adhesive were mixed uniformly in a weight ratio of 92:2.5:5.5 in an N-methylpyrrolidone solvent system, and then coated on an aluminum foil, dried, and cold pressed to obtain a positive electrode plate. The coating amount was 0.4 g / cm. 2 and the compaction density is 2.4 g / cm 3 It is.
[0198] The negative electrode active materials, artificial graphite, hard carbon, conductive agent acetylene black, adhesive styrene butadiene rubber (SBR), and thickener sodium carboxymethylcellulose (CMC), were mixed uniformly in deionized water in a weight ratio of 90:5:2:2:1, and then coated on copper foil, dried, and cold pressed to obtain a negative electrode plate. The coating amount was 0.2 g / cm. 2 and the compaction density is 1.7 g / cm 3 It is.
[0199] A polyethylene (PE) porous polymer film was used as a separator, and a positive electrode plate, a separator, and a negative electrode plate were stacked in order so that the separator was located in the center of the positive and negative electrodes to play the role of isolation, and then rolled up to obtain a bare cell. The bare cell was placed in an exterior body, and the same electrolyte as that used to manufacture the button cell described below was injected and packaged to obtain a full battery (hereinafter also referred to as a "full cell").
[0200] Button battery manufacturing The positive electrode active material, polyvinylidene fluoride (PVDF), and acetylene black were added to N-methylpyrrolidone (NMP) in a weight ratio of 90:5:5, and the mixture was stirred in a drying chamber to prepare a slurry. The slurry was coated on an aluminum foil, dried, and cold pressed to prepare a positive electrode plate. The coating amount was 0.2 g / cm. 2 and the compaction density is 2.0 g / cm 3 It is.
[0201] A lithium sheet was used as the negative electrode, and 1 mol / L LiPF6 was dissolved in ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1 as the electrolyte. Together with the positive electrode plate manufactured above, this was assembled into a button cell box as a button battery (hereinafter also referred to as a "button cell").
[0202] The positive electrode active material may be a first positive electrode active material, a second positive electrode active material, or a mixed positive electrode active material.
[0203] Material Performance Testing 1. Measurement of the chemical formula of the positive electrode active material A spherical aberrometer (ACSTEM) was used to characterize the internal microstructure and surface structure of the positive electrode active material with high spatial resolution, and the chemical formula of the positive electrode active material was obtained by combining with three-dimensional reconstruction technology.
[0204] 2. Lattice change rate measurement method In a constant temperature environment of 25°C, the positive electrode active material sample was placed in an XRD (model number is Bruker D8 Discover), and the sample was tested at 1° / min. The test data was analyzed and sorted, and the lattice constants a0, b0, c0 and v0 (a0, b0 and c0 represent the length of each side of the unit lattice, and v0 represents the volume of the unit lattice, which can be obtained directly from the XRD finishing result) were calculated by referring to the specification PDF card.
[0205] The positive electrode active material was prepared as a button cell according to the above "Preparation of Button Batteries", and the button cell was charged at a low rate of 0.05C until the current decreased to 0.01C. The positive electrode plate in the button cell was then taken out and placed in DMC for 8 hours for immersion. It was then dried, the powder was scraped off, and particles with a particle size of less than 500 nm were selected. The lattice constant v1 was calculated in the same manner as the fresh test sample above, and (v0-v1) / v0×100% was shown in the table as the lattice change rate before and after the lithium was completely released.
[0206] 3.Measuring method for Li / Mn antisite defect concentration The XRD results tested using the "Lattice Change Rate Measurement Method" were compared with the PDF (Powder Diffraction File) card of a standard crystal to obtain the Li / Mn antisite defect concentration. Specifically, the XRD results tested using the "Lattice Change Rate Measurement Method" were introduced into the General Structure Analysis System (GSAS) software, and the refinement results were automatically obtained. These included the occupancy status of different atoms, and the Li / Mn antisite defect concentration was obtained by reading the refinement results.
[0207] 4. Surface oxygen valence measurement method 5 g of the positive electrode active material sample was taken and fabricated into a button cell according to the above "Fabrication of Button Batteries". The button cell was charged at a low rate of 0.05 C until the current decreased to 0.01 C. The positive electrode plate in the button cell was then taken out and placed in DMC for 8 hours to soak. It was then dried, the powder was scraped off, and particles with a particle size of less than 500 nm were selected. The particles were measured by electron energy loss spectroscopy (EELS, the model number of the equipment used was Talos F200S) to obtain the energy loss near edge structure (ELNES), which reflected the state density and energy level distribution of the elements. The valence of the surface oxygen after charging was estimated by integrating the valence band state density data from the state density and energy level distribution and calculating the number of occupied electrons.
[0208] 5.Method of measuring consolidated density 5 g of the positive electrode active material powder was placed in a compaction mold (CARVER mold, model number 13 mm, USA), and the mold was placed on a compaction density meter. A pressure of 3 T was applied to the positive electrode active material, and the powder thickness at pressure (thickness after decompression) was read on the instrument, and the compaction density was calculated from ρ = m / v.
[0209] 6. Method for measuring the amount of Mn (and Fe doped into Mn sites) dissolved after cycling The positive electrode active material sample was fabricated as a full battery according to "Fabrication of a Full Battery" above.
[0210] The full battery, which had been cycled at 45°C until the capacity had decayed to 80%, was discharged at a rate of 0.1 C to a cut-off voltage of 2.0 V. The battery was then disassembled, the negative electrode plate was removed, and 30 unit area (1540.25 mm2) pieces were placed on the negative electrode plate. 2 ) wafers were randomly taken and tested for inductively coupled plasma emission spectrum (ICP) using an Agilent ICP-OES730. Based on the ICP results, the amount of Fe (if Fe is doped on the Mn site of the positive electrode active material) and Mn were calculated, and the amount of Mn (and Fe doped on the Mn site) dissolved after cycling was calculated accordingly. The test standard complies with EPA-6010D-2014.
[0211] 7.Measuring method for initial gram capacity of button battery The button battery was charged at 0.1 C from 2.5 to 4.3 V to 4.3 V. It was then charged at a constant voltage of 4.3 V until the current was 0.05 mA or less. It was left to stand for 5 minutes and discharged at 0.1 C to 2.0 V. The discharge capacity at this time was taken as the initial capacity and designated D0.
[0212] 8.3C constant current charging ratio measurement method In a constant temperature environment of 25°C, a fresh full battery was left standing for 5 minutes, then discharged at 1 / 3C to 2.5V. It was left standing for 5 minutes, then charged at 1 / 3C to 4.3V. It was then charged at a constant voltage of 4.3V until the current was 0.05mA or less. It was left standing for 5 minutes, and the charge capacity at this time was recorded as C0. It was discharged at 1 / 3C to 2.5V, left standing for 5 minutes, then charged at 3C to 4.3V, left standing for 5 minutes, and the charge capacity at this time was recorded as C1. The constant current charging ratio at 3C is C1 / C0 x 100%.
[0213] The higher the charging constant current ratio at 3C, the better the rate performance of the battery.
[0214] 9. Cycle performance test of full battery at 45℃ In a constant temperature environment of 45°C, the full battery was charged at 1C from 2.5 to 4.3V up to 4.3V. It was then charged at a constant voltage of 4.3V until the current was 0.05mA or less. It was left to stand for 5min, and then discharged at 1C down to 2.5V, and the discharge capacity at this time was recorded as D0. The above charge-discharge cycle was repeated until the discharge capacity decreased to 80% of D0. The number of cycles the battery had gone through was recorded.
[0215] 10. Full battery expansion test at 60℃ The full battery was stored at 60°C with a state of charge (SOC) of 100%. Before, during and after storage, the open circuit voltage (OCV) and internal resistance (IMP) of the cell were measured to monitor the SOC, and the cell volume was also measured. Here, after every 48 hours of storage, the full battery was taken out and left to stand for 1 hour before testing the open circuit voltage (OCV) and internal resistance (IMP). After cooling to room temperature, the cell volume was measured using the drainage method. In the drainage method, the gravity F1 of the cell was measured independently using a balance that automatically converts units using the dial data, and the cell was then completely immersed in deionized water (density 1 g / cm). 3 The cell is then placed in a container (known as a container for storing liquid) and the gravity F2 of the cell is measured. The buoyancy force F 浮 is F1-F2, and Archimedes principle F 浮 =ρ×g×V 排 Based on this, the cell volume V = (F1 - F2) / (ρ × g) was calculated.
[0216] From the results of the OCV and IMP tests, the batteries of the present embodiment always maintained an SOC of 99% or more until the end of storage in this experimental process.
[0217] After storage for 30 days, the cell volume was measured, and the increase rate of the cell volume after storage relative to the cell volume before storage was calculated.
[0218] The remaining capacity of the cell was also measured. A full battery was charged at 1C from 2.5 to 4.3V up to 4.3V. Then, at 4.3V, constant voltage charging was performed until the current became 0.05mA or less. The battery was left to stand for 5 minutes, and the charge capacity at this time was recorded as the remaining capacity of the cell.
[0219] 11. Specific surface area (BET) measurement method In accordance with GB / T 19587-2004, the specific surface area test was performed on the positive electrode active material using a specific surface area and porosity analyzer TRISTAR II 3020 (Micromeritics, USA). Before the test, the positive electrode active material was placed in a vacuum oven and dried at 200°C for ≥2h, with the sample weight >20g.
[0220] 12.Particleness D v 50 Tests The particle size D of the positive electrode active material was measured using a Mastersizer 3000 laser diffraction particle size analyzer (Malvern Panalytical) in accordance with GB / T19077-2016. v 50 was measured. Here, deionized water was used as a solvent, and the positive electrode active material was ultrasonically treated for 5 minutes before the test.
[0221] 13. ICP Test (Inductively Coupled Plasma Atomic Emission Spectroscopy) The elemental content tests were performed using an iCAP 7400 inductively coupled plasma optical emission spectrometer in accordance with EPA 6010D-2014. Aqua regia was selected as the solvent. Formula for calculating powder element content: Element content (mass%) = 100% × element mass / sample mass; formula for calculating plate element content: Element content (mass%) = 100% × element mass / (sample mass - collector mass).
[0222] 14. Li2CO3 and LiOH content test (free lithium potential titration test) The test was carried out using a 905 potentiometer in accordance with GB / T 9736-2008. After sampling, the samples were immediately vacuum sealed in aluminum plastic film bags. The minimum sample size for one test was ≥ 30g.
[0223] 15.Crystal type test Unless otherwise specified, in this application, the terms "single crystal / single crystal-like particles", "quasi-single crystal particles", "single crystal particles", "single crystal material particles" and similar expressions have essentially the same meaning and refer to single particles (i.e., primary particles) and / or agglomerated particles, among which agglomerated particles are particles formed by agglomeration of 100 or less (particularly about 5 to 50) primary particles having an average particle size in the range of 50 nm to 10,000 nm.
[0224] Unless otherwise specified, in this application, the terms "secondary particles" and "polycrystalline material particles" have generally similar meanings and refer to particles formed by aggregation of more than 100 primary particles having an average particle size in the range of 50-800 nm.
[0225] The positive electrode active material was examined using a scanning electron microscope. The sample and magnification were adjusted so that there were more than 10 aggregate particles in the field of view, the number of primary particles constituting each aggregate particle was counted, and the longitudinal size of the primary particles was measured on a scale to determine the particle size. The particle size of the primary particles in each aggregate particle was sorted in ascending order, the data with the largest particle size of 1 / 10 and the data with the smallest particle size of 1 / 10 were removed, and the average of the remaining particle size data was taken as the average particle size of the primary particles in this aggregate particle. If the number and average particle size of primary particles in 50% or more (including 50%) of the aggregate particles met the above definition of "polycrystalline material particles," the positive electrode active material was determined to be a polycrystalline material, and if not, it was determined to be a single crystal or single crystal-like material.
[0226] Here, SEM photographs of the first positive electrode active materials produced in Production Example A10 and Production Example A15 are as shown in FIG. 7-8.
[0227] 16. Hot Box Safety Test The test was conducted based on the "heating" section of the safety test in GB 38031-2020, and the upper limit was explored. The optimized test conditions are as follows:
[0228] <1> Prerequisites: Test conditions: An explosion-proof oven capable of heating the wiring connection port was prepared. The test cell was a fresh bare cell (cycle count ≦10), with temperature-sensing wires attached to the periphery of the cell and at positions such as the poles for temperature monitoring, and a temperature recording device was also installed. Cell treatment before testing: Constant current constant voltage charging was performed at a rate current of 0.33C to fully charge the cell to the nominal voltage (for example, in the present invention, the voltage is 4.3V).
[0229] <2> Test process: The sample was placed in a high-temperature bath, and the bath was heated from room temperature to 100°C at 5°C / min, and maintained at that temperature for 2 hours. The temperature was then further increased at 5°C / min, and maintained for 30 minutes at each 5°C interval, until the cell went out of control (runaway standard: voltage drop ≧50% within 1 min, cell temperature rise ≧50% within 1 min) or until the cell reached 200°C, at which point heating was stopped.
[0230] <3> Data processing: Based on the above conditions, the failure point was found, and the corresponding incubation temperature and incubation time were obtained. Time@temperature, for example, 21min@150℃.
[0231] <4> Benchmark results: The longer the duration of the test, the safer the sample is. The longer the duration of the test, the safer the sample may be, for example, a sample with the same failure point temperature but a longer time, a sample with the same failure point time but a higher temperature, or a sample with different failure point temperatures and times but a higher temperature.
[0232] [Table 5] JPEG2025502322000011.jpg143169
[0233] [Table 6]
[0234] [Table 7]
[0235] [Table 8]
[0236] [Table 9]
[0237] [Table 10]
[0238] [Table 11]
[0239] As can be seen from Tables 7, 9, 10, and 11 above, the second positive electrode active material of the present invention achieved more favorable effects than the comparative examples in one or all of cycle performance, high temperature stability, gram capacity, and compaction density.
[0240] As can be seen from the comparison between Manufacturing Examples B18-B20 and B23-B25, when other elements are the same, if (1-y):y is within the range of 1 to 4, the energy density and cycle performance of the secondary battery can be further improved.
[0241] [Table 12] JPEG2025502322000019.jpg249169
[0242] As can be seen from the comparison between Examples 1-43 and Comparative Example 1 in Table 12, the secondary batteries produced by mixing the first positive electrode active material and the second positive electrode active material of the present application have higher cycle capacity retention rates and longer cycle lives than the secondary battery produced in Comparative Example 1. In addition, the safety of the secondary batteries produced using the mixed positive electrode active materials of Examples 1, 3-7, 9, 12-13, 23-25, and 28 of the present application is superior to that of the secondary battery produced in Comparative Example 1.
[0243] As can be seen from a comparison between Examples 16 and 23-29, the cycle capacity retention rate of a secondary battery manufactured in which the value of the mass relationship m1 / (m1+m2) between the first positive electrode active material and the second positive electrode active material of the present application is between 3% and 50% is further improved, and the cycle life is further extended. A secondary battery manufactured in which the value of the mass relationship b×m1 / m1+m2 between the first positive electrode active material and the second positive electrode active material of the present application is 0.457 or less has a high cycle capacity retention rate, a long cycle life, and high safety. As can be seen from a comparison between Examples 16 and 23-29, a secondary battery manufactured in which the value of the mass relationship b×m1 / (m1+m2) between the first positive electrode active material and the second positive electrode active material of the present application is within the range of 0.025 to 0.415 further improves the cycle capacity retention rate, further extends the cycle life, and further improves safety.
[0244] As can be seen from the comparison of Examples 1-11 and 22, when the first positive electrode active material of the present application is single crystal-like, the D v 50 The secondary battery manufactured with a particle size of 5.8 μm or less has a high cycle capacity retention rate, a long cycle life, and high safety. v The secondary batteries manufactured with a particle size of 4.3 μm or less had a higher cycle capacity retention rate and a longer cycle life.
[0245] As can be seen from the comparison of Examples 12-21, when the first positive electrode active material of the present application is polycrystalline, the D v 50 Particle size is 3.5 to 13.5 μm, and the BET specific surface area is 1.32 m 2 / g or less and the compaction density at 3T pressure is 2.92 g / cm 3 The secondary battery thus prepared had a higher cycle capacity retention rate and a longer cycle life.
[0246] As can be seen from the comparison of Examples 1-8, 10-11, and 22, when the first positive electrode active material of the present application is single crystal-like, the first positive electrode active material LiNi b Co d Mn e M f The secondary batteries manufactured with d in O2 selected from the range of 0.047 to 0.320 had higher cycle capacity retention and longer cycle life.
[0247] The first positive electrode active material of the present application is LiNi b Co d Mn e M f The secondary batteries manufactured by selecting b in O2 from the range of 0.314 to 0.970 had high cycle capacity retention, long cycle life, and high safety. As can be seen from the comparison of Examples 1-11 and 22, when the first positive electrode active material was a single crystal or pseudo single crystal material, the secondary batteries manufactured by setting b to a value greater than 0.314 and less than 0.97 (excluding the values of 0.314 and 0.97) had higher cycle capacity retention and longer cycle life.
[0248] As can be seen from the comparison between Examples 10 and 22, the secondary battery manufactured using the first positive electrode active material of the present application having a lithium carbonate mass content of 1% or less and a lithium hydroxide mass content of 1% or less had a higher cycle capacity retention rate, a longer cycle life, and higher safety.
[0249] As can be seen from a comparison between Tables 5 and 12, the safety of the secondary battery prepared using the mixed cathode active material containing the corresponding first cathode active material of the present application was higher than that of the secondary battery prepared using the first cathode active material, and the cycle capacity retention rate of the secondary battery prepared using the mixed cathode active material containing the corresponding first cathode active material of the present application was higher and the cycle life was longer than that of the secondary batteries prepared using the first cathode active materials of Preparation Examples A14-A17 and A19-A21.
[0250] As can be seen from a comparison of Tables 7, 9, 10, and 11 with Table 12, the secondary batteries prepared using the mixed positive electrode active material containing the corresponding second positive electrode active material of the present application had higher cycle capacity retention rates and longer cycle lives than the secondary batteries prepared using the second positive electrode active materials of Preparation Examples B1, B14, B16, B25, B26, B27, B31, B47, and B55-B60.
[0251] It should be noted that the present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment having substantially the same configuration as the technical idea and achieving the same effect within the scope of the technical solution of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can make to the embodiment and other methods configured by combining some of the components in the embodiment are also included in the scope of the present application, within the scope of the purpose of the present application. [Explanation of symbols]
[0252] 1 battery pack, 2 upper housing, 3 lower housing, 4 battery module, 5 secondary battery, 51 case, 52 electrode assembly, 53 cover plate
Claims
1. A positive electrode active material including a first positive electrode active material and a second positive electrode active material, The first positive electrode active material is the compound LiNi b Co d Mn e M f O 2 wherein b is selected from the range of 0.314 to 0.970, d is selected from the range of 0 to 0.320, optionally selected from the range of 0.047 to 0.320, e is selected from the range of 0.006 to 0.390, the sum of b, d, e and f is 1 and f is greater than 0, M is one or more elements selected from Mn, Al, Mg, Ca, Na, Ti, W, Zr, Sr, Cr, Zn, Ba, B (boron), S and Y, optionally M is Mg and / or Al; The second positive electrode active material is a compound Li a A x Mn 1-y B y P 1-z C z O 4-n D n a is selected from the range of 0.9 to 1.1, x is selected from the range of 0.001 to 0.1, y is selected from the range of 0.001 to 0.5, z is selected from the range of 0.001 to 0.1, n is selected from the range of 0.001 to 0.1, A is one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo, and W, B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge, C is one or more elements selected from B (boron), S, Si, and N, and D is one or more elements selected from S, F, Cl, and Br.
2. The mass of the first positive electrode active material is m 1 and the mass of the second positive electrode active material is m 2 And m 1 / (m 1 +m 2 2. The cathode active material of claim 1, wherein the value of is 2% to 55%, and optionally 3% to 50%.
3. b x m 1 / (m 1 +m 2 3. The positive electrode active material according to claim 1, wherein the value of is 0.017 to 0.457, and optionally 0.025 to 0.
415.
4. The first positive electrode active material is a single crystal or pseudo single crystal material, and the particle size D of the first positive electrode active material is v 4. The positive electrode active material according to claim 1, wherein 50 is 5.8 μm or less, optionally 2.3 to 5.8 μm, and further optionally 2.3 to 4.3 μm.
5. When the first positive electrode active material is a single crystal or pseudo-single crystal material, and / or, d is selected from the range of 0.05 to 0.320, optionally selected from the range of 0.05 to 0.282; The positive electrode active material according to any one of claims 1 to 4, wherein b is greater than 0.314 and less than 0.97, and is selectively selected from the range of 0.55 to 0.
869.
6. When the first positive electrode active material is a polycrystalline material, the particle diameter D of the first positive electrode active material v 50 is 3.0 to 13.5 μm, optionally 3.5 to 13.5 μm; and / or The BET specific surface area of the first positive electrode active material is 1.73 m 2 / g or less, and optionally 1.32 m 2 / g or less, and more preferably 0.28 to 1.32 m 2 / g, and / or The compaction density of the first positive electrode active material at a pressure of 3 T is 2.90 g / cm 3 or more, and optionally 2.92 g / cm 3 or more, and more selectively, 2.92 to 3.31 g / cm 3 The positive electrode active material according to claim 1 ,
7. The first positive electrode active material further contains lithium carbonate and / or lithium hydroxide, 7. The cathode active material according to claim 1, wherein the mass content of the lithium carbonate is 1.05% or less, and optionally 1% or less, and / or the mass content of the lithium hydroxide is 1.02% or less, and optionally 1% or less, based on the mass of the first cathode active material.
8. A is any one element selected from Zn, Al, Na, K, Mg, Nb, Mo and W, B is at least two elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, C is any one element selected from B (boron), S, Si and N, D is any one element selected from S, F, Cl and Br, and optionally A is Mg or Nb, and / or The B is at least two elements selected from Fe, Ti, V, Co and Mg, and optionally Fe, and one or more elements selected from Ti, V, Co and Mg; and / or C is S; and / or The positive electrode active material according to claim 1 , wherein D is F.
9. and / or, x is selected from the range of 0.001 to 0.005; and / or y is selected from the range of 0.01 to 0.5, optionally selected from the range of 0.25 to 0.5; and / or z is selected from the range of 0.001 to 0.005; The positive electrode active material according to any one of claims 1 to 8, wherein n is selected from the range of 0.001 to 0.
005.
10. (1-y): The value of y is selected from the range of 1 to 4, and optionally from the range of 1.5 to 3; and a: The value of x is selected from the range of 9 to 1100, and optionally from the range of 190 to 998. The positive electrode active material according to any one of claims 1 to 9.
11. The positive electrode active material according to any one of claims 1 to 10, wherein the second positive electrode active material has a lattice change rate before and after complete lithium release of 8% or less, and optionally 4% or less.
12. 12. The cathode active material of claim 1, wherein the second cathode active material has a Li / Mn antisite defect concentration of 2% or less, optionally 0.5% or less.
13. The cathode active material according to any one of claims 1 to 12, wherein the surface oxygen valence of the second cathode active material is -1.82 or less, and optionally -1.89 to -1.
98.
14. The compaction density of the second positive electrode active material at 3 T is 2.0 g / cm 3 or more, and optionally 2.2 g / cm 3 The positive electrode active material according to claim 1 .
15. The positive electrode active material according to any one of claims 1 to 14, wherein the second positive electrode active material further comprises carbon, and the carbon is coated on a surface of the compound LiaAxMn1-yByP1-zCzO4-nDn.
16. A method for producing a positive electrode active material, comprising the steps of: providing a first active cathode material and a second active cathode material; mixing the first positive electrode active material with the second positive electrode active material; The first positive electrode active material is the compound LiNi b Co d Mn e M f O 2 The second positive electrode active material comprises the compound Li a A x Mn 1-y B y P 1-z C z O 4-n D n wherein the definitions of a, b, d, e, f, x, y, z, n, M, A, B, C and D are as set out in any one of claims 1 to 15; Optionally, the first positive electrode active material further comprises lithium carbonate and / or lithium hydroxide; Optionally, the second positive electrode active material is the compound Li a A x Mn 1-y B y P 1-z C z O 4-n D n The method for producing a positive electrode active material further comprises coating carbon on the surface of the positive electrode active material.
17. A positive electrode plate comprising: a positive electrode current collector; and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer comprising the positive electrode active material according to any one of claims 1 to 15 or the positive electrode active material produced by the method according to claim 16, and optionally, a content of the positive electrode active material in the positive electrode film layer is 10 wt % or more, and further optionally, 95 to 99.5 wt %, based on a total weight of the positive electrode film layer.
18. A secondary battery comprising the positive electrode active material according to any one of claims 1 to 15, the positive electrode active material produced by the method according to claim 16, or the positive electrode plate according to claim 17.
19. A battery module comprising the secondary battery according to claim 18.
20. A battery pack comprising the battery module according to claim 19.
21. A power consuming device comprising at least one selected from the group consisting of the secondary battery according to claim 18, the battery module according to claim 19, and the battery pack according to claim 20.
Citation Information
Patent Citations
Security lithium ion battery positive plate as well as preparation method thereof
CN103811727A
Lithium ion battery positive electrode material with adjustable crystalline grain size and preparation method thereof
CN105118985A
Positive electrode active material and nonaqueous electrolyte secondary battery
JP2002198050A
Nonaqueous electrolyte secondary battery
JP2010129332A
Positive electrode for battery
JP2014082050A